CuO decorated natural rectorite as highly efficient catalyst for photoinduced peroxymonosulfate activation towards tetracycline degradation. (1st October 2021) - Yi, Lian; Li, Yubiao; Zhu, Liangliang; Gao, Caiyan; Wu, Xiaoyong
Abstract: Developing a low-cost and excellent catalyst for advanced oxidation process (AOPs) to degrade refractory organic contaminants is still an urgent problem. In this work, a copper oxide decorated natural rectorite (Cu-R) catalyst was successfully synthesized by a facile impregnation method. Intriguingly, Cu-R possessed excellent performance in removing tetracycline (TC) through photoinduced peroxymonosulfate (PMS) activation, and its reaction rate constants were ca. 4.3 times and 7.0 times that of Fe2 O3 and Co3 O4, respectively. Moreover, the effects of reaction parameters on the photoinduced Cu-R activation of PMS to degrade TC were investigated in detail. The results showed that the system exhibited excellent impact resistance to Cl −, HCO3 − and NO3 − in aqueous solution. Cu-R could not only exhibit excellent removal of TC in a wide pH range of 5–9, but also maintain the stability of the catalyst. The electron paramagnetic resonance test and quenching experiments proved that the excellent TC removal ability could be mainly attributed to the synergistic effect between CuO and rectorite under the assistant of light, which was beneficial for the activation of PMS and then produced a large number of active radicals such as OH and O2 - . Importantly, a possible path for TC degradation was given by the LC-MS analysis. The prepared Cu-R can provide a low-cost, high-efficiency and promising catalyst for the treatment of antibiotic wastewater by PMS activation with photoassistent. Highlights: Copper oxide decorated natural rectorite was synthesized by a facile impregnation method. Cu-R exhibited a higher TC degradation efficiency than CuO and rectorite alone. The synergistic effect of rectorite and CuO resulted in outstanding catalytic activity. The .OH of rectorite inhibited the leaching of copper ions.